Analysis of wound exudates reveals differences in the patterns of tissue damage and inflammation induced by the venoms of Daboia russelii and Bothrops asper in mice. (30th October 2020) - Rucavado, Alexandra; Escalante, Teresa; Kalogeropoulos, Konstantinos; Camacho, Erika; Gutiérrez, José María; Fox, Jay W.
Abstract: Clinical manifestations of envenomings by bites of the viperid snakes Bothrops asper and Daboia russelii show marked differences. Both venoms elicit the typical effects induced by viperid venoms (local tissue damage, bleeding, coagulopathies, shock). In addition, envenomings by D. russelii are characterized by a high incidence of acute kidney injury and by systemic capillary leak syndrome. The present investigation aimed to compare the local pathological and inflammatory events induced by the intramuscular injection of these venoms in a mouse model. B. asper venom induced stronger local hemorrhage, whereas D. russelii venom caused a higher extent of myonecrosis, and both venoms induced inflammation. Exudates collected from the site of tissue damage showed higher proteolytic activity in the case of samples from B. asper venom-treated mice. This activity was abrogated by antivenoms, indicating that it is the result of the action of venom proteinases. In addition, an increase in matrix metalloproteinases (MMPs) over time was detected in exudates induced by both venoms. Proteome analysis of exudates revealed higher abundance of extracellular matrix (ECM)-derived protein fragments in samples collected from B. asper venom-injected mice, whereas those from D. russelii venom-injected animals had higher amounts of intracellular proteins. Analysis of the subproteome of inflammatory mediators in exudates showed various patterns of change over time. Some mediators peaked at 180 min and decreased afterwards, whereas others increased and remained elevated during the 360 min observation period. Interestingly, various mediators (MIP-1α, MIP-1β, KC, MIP-2, GM-CSF, VEGF, and LIX) increased and then decreased in the case of B. asper venom, while they remained elevated at 360 min in the case of D. russelii venom. Our findings show that these venoms induce a different pattern of local tissue damage and suggest that the venom of D. russelii induces a more sustained inflammatory reaction, an observation that may have implications for the pathophysiology of envenomings. Graphical abstract: Image 1 Highlights: The venoms of the viperid snakes Bothrops asper and Daboia russelii differ in their pathological and inflammatory effects. Exudates from tissue injected with B. asper venom showed higher amounts of fragments from extracellular matrix proteins. Exudates from tissue injected with D. russelii venom showed higher amounts of fragments from cytosolic proteins. The time course of increase of inflammatory mediators differ in exudates from mice injected with these venoms.